Study of frequency and histopathological pattern of soft tissue tumours in tertiary care centre of Gandhinagar, Gujarat - Dr. Amita Patel; Dr. Vandana Naranbhai Patel (Tropical Journal of Pathology and Microbiology, 2019)
Background: Ovaries are complex intra-pelvic organs of the female reproductive system. Ovarian cancer accounts for 3% of all cancers in females and is the fifth most common cause of cancer death in women. Early menarche, late menopause, nulliparity and high socioeconomic status are associated with an increased risk for ovarian neoplasms. Histo-pathological diagnosis remains the mainstay to differentiate neoplastic lesions from non-neoplastic lesions. Aims and objectives: This study aims to analyze the view of ovarian tumors with respect to clinical presentation, gross and microscopic characteristics and also to study the frequency and histopathological patterns of ovarian tumours. Materials and Methods: This study comprised of 100 cases of ovarian tumours received in the Department of Pathology, GMERS Medical College, Gandhinagar were analysed. Their gross features, microscopic findings were analysed in detail. Ovarian tumours were divided into benign and malignant categories and their further sub typing were done according to WHO Classification. Results: Out of total 100 cases, 76 were benign and 24 were malignant. Out of 100 cases, 62% were between 21-40 years of age followed by 28% were between 41-60 years of age. Most common presenting symptom was pain in abdomen followed by lump in abdomen and heavy menstruation. Out of total 100 cases, 70% were surface epithelial tumours, 24% were germ cell tumours and 6% were sex cord stromal tumours. Conclusion: To conclude we recommend microscopic histopathological examination of every ovarian mass in order to assess the importance of pathological grading and staging and they must be classified correctly so that the patient can be provided with appropriate treatment and prognosis.